Conservation of Rice Terraces in Japan - Roles of the Sakaori Rice Terrace Conservation Association - Kobayashi , Koji; Harada, Chisato (Journal for Geography, 2010)
Since the 1960s, many farming fields have been left abandoned in Japan. However, rice terrace conservation activities have been spreading extensively in recent years as many people have reconfirmed the multi-functionality of rice terraces in Japan. This paper introduces rice terraces in the Sakaori District of Gifu Prefecture in Japan, and describes the current state of conservation activities as well as challenges ahead that people will face in preserving rice terraces in Japan. It is shown that the efforts and contributions of the Sakaori Rice Terrace Conservation Association members are the primary driving force for conservation and development of the rice terraces in the Sakaori District. However, it is also noteworthy that the farming workforce supporting the Sakaori Rice Terrace Conservation Association is continually diminishing and that the aging of this workforce is causing serious problems as well.
Keywords: rice terrace (tanada); farming villages; the Sakaori Rice Terrace Conservation Association; rice terrace ownership system